2022
DOI: 10.1186/s12916-022-02452-8
|View full text |Cite
|
Sign up to set email alerts
|

The accuracy of pulse oximetry in measuring oxygen saturation by levels of skin pigmentation: a systematic review and meta-analysis

Abstract: Background During the COVID-19 pandemic, there have been concerns regarding potential bias in pulse oximetry measurements for people with high levels of skin pigmentation. We systematically reviewed the effects of skin pigmentation on the accuracy of oxygen saturation measurement by pulse oximetry (SpO2) compared with the gold standard SaO2 measured by CO-oximetry. Methods We searched Ovid MEDLINE, Ovid Embase, EBSCO CINAHL, ClinicalTrials.gov, and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
55
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(56 citation statements)
references
References 54 publications
0
55
0
1
Order By: Relevance
“…The impact of hypoxemia on the measure of SpO 2 is a well-known issue [ 34 ]. It has been reported that the poor quality of the measure of hypoxemic patients could be related 1/to the arteriolar dilation caused by tissue hypoxia that induces venous pulsation, which reduces the quality of the measure [ 9 , 35 ], 2/with the quality of the pulse oximeter being used [ 35 , 36 ] or high levels of skin pigmentation [ 14 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of hypoxemia on the measure of SpO 2 is a well-known issue [ 34 ]. It has been reported that the poor quality of the measure of hypoxemic patients could be related 1/to the arteriolar dilation caused by tissue hypoxia that induces venous pulsation, which reduces the quality of the measure [ 9 , 35 ], 2/with the quality of the pulse oximeter being used [ 35 , 36 ] or high levels of skin pigmentation [ 14 , 37 , 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…AHI, however, proved to be equivalent regardless of the hypopnea criteria used in its definition (AASM 2012, Chicago) [ 43 ]. Fifth, we evaluated a white race population, so the diagnostic performance of oximetry cannot be extrapolated to subjects with dark skin pigmentation [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
“…In a 2022 meta-analysis of 382 articles, only 15 articles assessed the impact of skin pigmentation on pulse oximeter accuracy. 8 The qualitative categories were not specific: light, medium, and dark. 8 Colorimeters and spectrophotometers, which measure erythema and melanin indices in addition to other relevant pigment parameters, are highly useful in parsing the mechanisms that drive the observed associations between skin pigment and pulse oximeter errors.…”
Section: On the Topic Of Pigmentmentioning
confidence: 99%
“…8 The qualitative categories were not specific: light, medium, and dark. 8 Colorimeters and spectrophotometers, which measure erythema and melanin indices in addition to other relevant pigment parameters, are highly useful in parsing the mechanisms that drive the observed associations between skin pigment and pulse oximeter errors. Most importantly, these quantitative data can inform efforts to improve pulse oximeter technology and hone regulatory approaches to address the observed biases.…”
Section: On the Topic Of Pigmentmentioning
confidence: 99%